Uma oficina para formação de professores com enfoque em quadriláteros - Maioli, Marcia (2002)
This work is about Mathematics teacher education. It ains to offer a contribution in this area, in terms of understanding the processes by which new mathematical content is adquired and existing knowledge extended. We hope that it helps teachers to develop suitable strategies for working with Geometry in the classroom. This study is founded in BROUSSEAU s theory of situations and in DUVAL s studies about the use of several registers of semiotic representation. We prepared a workshop composed of activities whose focus was quadrilaterals, which was attended by a group of teachers from elementary and secondary school levels. During the workshop, we discussed the theoretical references that had served as a base for selectiing the activities and for the manners in which these were presented. The research question is: how can we work with teachers in ways which result in the acquisition of geometrical knwledge and, at the some time, provide them with inherent didactic knowledge related the geometrical content? Our main hypothesis is that the proposed activities will contribute to the content acquisition and the discussion of the theoretical references to the didactic knowledge improvement. Analyses of the teachers behavior and discussion, during 33 workshop hours, reveals that the activities provoked considerations about definitions, assumpitions, properties of quadrilaterals, theorems and proofs, as well as helping teachers to discover the difficulties they have in using different registers of representation in Geometry. The discussion of the theoretical references made the teachers understand that in their classroom they have usually omitted the action, formulation and validity stages, discussed by BROUSSEAU, presenting Geometry in an institutionalized way